ASUHAN KEPERAWATAN DEMENSIA PADA NY. N DENGAN PERUBAHAN PROSES PIKIR DI WILAYAH KERJA PUSKESMAS TANJUNG BUNTUNG - Hayat, Nahrul; Rahmadeni, Asfri Sri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Dementia is a disorder that occurs in the elderly as a result of physiological changes in the form of cognitive decline. Dementia affects about 10% of those over 65 years and 47% over 85 years. In Indonesia, the prevalence of dementia in elderly people aged 65 years is 5% of the elderly population. This prevalence increases to 20% in elderly people aged 85 years and over. The purpose of writing a proposal for the implementation of nursing care in patients with dementia with altered thought processes. This research is a descriptive study with a case study design, respondents consisted of one respondent carried out on August 4-6, 2020. The data collection methods used were interviews, observation, and documentation. The results of the research after giving nursing care, the authors carried out the appropriate nursing actions in the action plan until the third day. For more accurate results it is advisable to further study the elderly with dementia, especially for diagnostic tests, and pay attention to the management of pharmacological and non-pharmacological therapies, as well as complete documentation.Keywords: Gerontic Nursing Care, Dementia, Thought Process Disorders